2022
DOI: 10.3390/pathogens11070777
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Mycobacteriophages: From Classification to Applications

Abstract: Mycobacterial infections are a group of life-threatening conditions triggered by fast- or slow-growing mycobacteria. Some mycobacteria, such as Mycobacterium tuberculosis, promote the deaths of millions of lives throughout the world annually. The control of mycobacterial infections is influenced by the challenges faced in the diagnosis of these bacteria and the capability of these pathogens to develop resistance against common antibiotics. Detection of mycobacterial infections is always demanding due to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…Actinobacteria phages are increasingly being developed as therapeutics for treating bacterial infections ( 1 ). To shed more light on the ecology and diversity of actinobacteriophages, here we report on bacteriophage Alucard, isolated using Microbacterium foliorum (NRRL B-24224), that contains no detectable prophages or CRISPR systems and is therefore ideal as an isolation host ( 2 ).…”
Section: Announcementmentioning
confidence: 99%
“…Actinobacteria phages are increasingly being developed as therapeutics for treating bacterial infections ( 1 ). To shed more light on the ecology and diversity of actinobacteriophages, here we report on bacteriophage Alucard, isolated using Microbacterium foliorum (NRRL B-24224), that contains no detectable prophages or CRISPR systems and is therefore ideal as an isolation host ( 2 ).…”
Section: Announcementmentioning
confidence: 99%
“…The role of mycobacteriophages and their derived endolysins in human therapy has gained attention, especially in the last few years when mycobacteriophages were used to treat drug-resistant NTM infections [25,26]. Phages and endolysins can also play an important role in potentially shortening the treatment regimen of TB/NTM infections [9,27]. The mycobacterial cell envelope is more elaborate when compared to Gram-positive and Gram-negative bacteria; it contains an additional mycolylarabinogalactan layer, which forms an ester linkage with the peptidoglycan.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the 2022 World Health Organization (WHO) report on tuberculosis (TB), the proportion of multi-drug resistant cases was estimated as being 20% in 2021, and almost 43% of MDR-TB cases were treated between 2018 and 2021 [ 12 ]. Mycobacteriophages, either in isolation or as a cocktail, or as part of a synergistic therapy with antibiotics, have potential in the treatment of mycobacterial infections [ 13 ]. It is reported that 20 patients with antibiotic-refractory mycobacterial infections received treatment with a mycobacteriophage cocktail [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Jessica S. Little and her team reported a case of a 56-year-old patient with a refractory disseminated cutaneous Mycobacterium chelonae infection, who received mycobacteriophage therapy, and experienced a significant improvement in their skin lesions [ 15 ]. Mycobacteriophages can also be utilized as a tool for engineering shuttle plasmids to detect drug-resistant M. tuberculosis strains, including DS6A and TM4-based shuttle plasmids [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%